New figures on unfunded public pension entitlements across Europe: Concept, results and applications - Klaus Kaier; Christoph Müller (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2013)
A major aim of the recent updates of National Accounting standards (SNA2008 and ESA2010) is to provide a more complete picture of households' wealth. In this course it will become mandatory for European countries to publish annual estimates of unfunded public pension entitlements (UPPE) from 2017 onwards. This study describes the methodological concepts behind this new figure of national accounts. After a review of past studies on the subject of UPPE we provide a large cross-country comparison for 18 EU countries of this new pension wealth figures and discuss a number of possible applications for policy makers and researchers. This includes the use to estimate the offset between UPPE and savings (Feldstein 1974). Finally, we show the distribution of households' wealth across Europe including financial wealth, dwellings and UPPE. Many prosperity differences between countries with Beveridgean and Bismarkian pension systems as well as between western and central eastern European countries are eliminated when considering these three wealth categories. In addition, a direct comparison of UPPE with replacement rates shows that these two proxies for the generosity of pension systems are completely uncorrelated at the cross-country level.
Keywords: E21; H55; H63; 330; households' wealth; pension liabilities; pension entitlements; household saving